Stroke volume and cardiac output non-invasive monitoring based on brachial oscillometry-derived pulse contour analysis: Explanatory variables and reference intervals throughout life (3–88 years) - Zócalo, Yanina (2020)
Background: Non-invasive assessment of stroke volume (SV), cardiac output (CO) and cardiac index (CI) has shown to be useful for the evaluation, diagnosis and/or management of different clinical conditions. Through pulse contour analysis (PCA) cuff-based oscillometric devices would enable obtaining ambulatory operator-independent non-invasive hemodynamic monitoring. There are no reference intervals (RIs), when considered as a continuum in childhood, adolescence and adult life, for PCA-derived SV [SV(PCA)], CO [CO(PCA)] and CI [CI(PCA)]. The aim of the study were to analyze the associations of SV(PCA), CO(PCA) and CI(PCA) with demographic, anthropometric, cardiovascular risk factors (CVRFs) and hemodynamic parameters, and to define RIs and percentile curves for SV(PCA), CO(PCA) and CI(PCA), considering the variables that should be considered when expressing them. Methods: In 1449 healthy subjects (3–88 years) SV(PCA), CO(PCA) and CI(PCA) were non-invasively obtained (Mobil-O-Graph; Germany). Analysis: associations between subject characteristics and SV(PCA), CO(PCA) and CI(PCA) levels (correlations; regression models); RIs and percentiles for SV(PCA), CO(PCA) and CI(PCA) (parametric methods; fractional polynomials). Results: Sex, age, and heart rate would be explanatory variables for SV, CO, and CI levels. SV levels were also examined by body height, while body surface area (BSA) contributing to evaluation of CO and CI. CVRFs exposure did not contribute to independently explain the values of the dependent variables. SV, CO and CI levels were partially explained by the oscillometric-derived signal quality. RIs and percentiles were defined. Conclusions: Reference intervals and percentile for SV(PCA), CO(PCA) and CI(PCA), were defined for subjects from 3–88 years of age, results are expressed according to sex, age, heart rate, body height and/or BSA.